Evaluating the time-dependent deformations and bond characteristics of a self-consolidating concrete mix and the implication for pretensioned[sic] bridge applications - Larson, Kyle Hatch (Kansas State University, 2006)
Results of an extensive experimental program conducted to determine the material, bond characteristics, and time-dependent deformations of a proposed self-consolidating concrete (SCC) mixture for bridge girders are presented. This research program was completed in a three-step process. The first phase consisted of 15 full-scale, pretensioned SCC flexural specimens that were tested to evaluate their transfer and development lengths. These specimens included both single-strand and multiple-strand beams, as well as specimens designed to evaluate the so-called “top-strand" effect. The top-strand specimens, with more than 20 inches of concrete below the strand, were tested to evaluate the current American Association of State Highway Officials requirement of a 30% increase development length when the concrete below the strand is more than 12 inches. Strand end-slip measurements, used to estimate transfer lengths, indicated the proposed SCC mixture meets ACI and AASHTO requirements. In addition, flexural tests confirmed the proposed SCC mixture also meets current code requirements for development length. The second step was to evaluate the elastic shortening, creep, and shrinkage properties of the proposed SCC mixture for bridge girders. Four bridge girders with an inverted-T profile were used to measure these time-dependent deformations. In two of the specimens, the strands were tensioned to 75% of ultimate tensile strength (representing a girder that would be put into service). Strands of the other two specimens were left untensioned to evaluate shrinkage effect of the concrete alone. The shrinkage was then subtracted from the fully tensioned specimens and elastic shortening and creep were isolated after relaxation losses were calculated from code expressions. In addition, the fully tensioned specimens were used to determine transfer lengths of the prestressing strand. The final step in the program was to record strain measurements in actual bridge girders used in the field. Elastic shortening, creep, and shrinkage prestress loss results of the proposed SCC mixture were compared with current design equations. Instrumentation of seven pretensioned girders in a five-span bridge located in Cowley County, Kansas, was used to measure time-dependent deformations. Three of these girders utilized SCC, while the other four were cast with conventional concrete.
Keywords: SCC; Transfer Length; Development Length; Time-Dependent Deformations; Bridge Monitoring; Engineering, Civil (0543)